2004
DOI: 10.1007/s11300-004-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Deposit Insurance, Institutions, and Bank Interest Rates

Abstract: Abstract:Many recent institutional reforms of the financial system have relied on the introduction of an explicit scheme of Deposit Insurance. This instrument aims at two main targets, contributing to systemic stability and protecting depositors. However it may also affect the interest rate spread in the banking system, which can be viewed as an indicator of market power in this financial segment. This paper provides an empirical investigation of the effect of deposit insurance and other institutional and econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
1
8
0
2
Order By: Relevance
“…In a study of Kansas, Wheelock and Wilson (1995) found out that deposit insurance membership increases the probability of bank failure, consistent with the hypothesis that insurance encourages banks to hold higher risk portfolios than they otherwise would. Similar …ndings are reported by Carapella and Di Giorgio (2004), who demonstrate that deposit insurance increases the lendingdeposit spread in banking, the main e¤ect of which arises not from the deposit side, but from an increase in the lending rate. They interpret this result as evidence of the presence of moral hazard behaviour emanating from deposit insurance.…”
Section: Moral Hazardsupporting
confidence: 85%
See 1 more Smart Citation
“…In a study of Kansas, Wheelock and Wilson (1995) found out that deposit insurance membership increases the probability of bank failure, consistent with the hypothesis that insurance encourages banks to hold higher risk portfolios than they otherwise would. Similar …ndings are reported by Carapella and Di Giorgio (2004), who demonstrate that deposit insurance increases the lendingdeposit spread in banking, the main e¤ect of which arises not from the deposit side, but from an increase in the lending rate. They interpret this result as evidence of the presence of moral hazard behaviour emanating from deposit insurance.…”
Section: Moral Hazardsupporting
confidence: 85%
“…Furthermore, they infer from their results that a more generous deposit insurance creates more moral hazard problems which in turn increase banking fragility. Related work with similar …ndings has been carried out by Wheelock and Wilson (1995), Carapella and Di Giorgio (2004) and Cull, Senbet and Sorge (2005), among others.…”
Section: Introductionmentioning
confidence: 56%
“…Another study that uses cross-country panel data between 1980 and 2004 also finds an effect of a deposit insurance scheme on bank insolvency and bank runs (Ngalawa et al 2016). A similar study also shows that the implementation of a deposit insurance scheme increases the likelihood of bank failure (Hooks and Robinson 2002), loan-deposit rate spread (Carapella and Giorgio 2004), and moral hazard (Yilmaz and Muslumov 2008).…”
Section: Introductionmentioning
confidence: 78%
“…In the absence of deposit insurance coverage, monitoring of banks by private parties increases and thus uninsured depositors tend to discipline banks by demanding higher deposit rates (Demirguc-Kunt and Kane, 2002;Anginer et al, 2013). Moreover, deposit insurance could also impact the lending rates positively, as bank managers might lend to customers of low creditworthiness suggesting that they would require higher interest rates for the loans provided (Carapella and Giorgio, 2004;Ioannidou and Penas, 2010). This could suggest that deposit insurance coverage might have a positive impact on bank profitability through its effect on interest margins.…”
Section: Deposit Coverage Insurance Ump and Bank Performancementioning
confidence: 99%
“…This reduction in interest margins because of the monitoring of depositors could be strengthened for deposit uninsured banks. Moreover, at the presence of lower margins over unconventional monetary policy periods, insured banks are encouraged to relax further their credit standards because of lack of private monitoring and thus increase lending to borrowers of low creditworthiness (Carapella and Giorgio, 2004;Ioannidou and Penas, 2010).…”
Section: Deposit Coverage Insurance Ump and Bank Performancementioning
confidence: 99%